Expression of fibroblast growth factor 10 and cognate receptors in the developing bovine ovary - Castilho, A. C. S. [UNESP]; Bueno da Silva, R. [UNESP]; Price, C. A.; Machado, M. F. [UNESP]; Amorim, Renée Laufer [UNESP]; Buratini, J. [UNESP] (Elsevier B.V., 2014)
In the mammalian ovary, FGF10 is expressed in oocytes and theca cells and is a candidate for paracrine signaling to the developing granulosa cells. To gain insight into the participation of FGF10 in the regulation of fetal folliculogenesis, we assessed mRNA expression patterns of FGF10 and its receptors, FGFR1B and FGFR2B, in relation to fetal follicle dynamics and localized FGF10 protein in bovine fetal ovaries at different ages. Primordial, primary, secondary, and antral follicles were first observed on Days 75, 90, 150, and 210 of gestation, respectively. The levels of GDF9 and BMP15 mRNA, markers for primordial and primary follicles, respectively, increased during fetal ovary development in a consistent manner with fetal follicle dynamics. CYP17A1 mRNA abundance increased from Day 60 to Day 75 and then from Day 120 to Day 150, coinciding with the appearance of secondary follicles. FGF10 mRNA abundance increased from Day 90, and this increase was temporally associated with increases in FGFR1B mRNA abundance and in the population of primary follicles. In contrast, FGFR2B mRNA expression was highest on Day 60 and decreased thereafter. FGF10 protein was localized to oogonia and oocytes and surrounding granulosa cells at all fetal ages. The present data suggest a role for FGF10 in the control of fetal folliculogenesis in cattle. (C) 2014 Published by Elsevier Inc.
Keywords: FGF10; Ovary; Preantral follicles; Oogonia; Bovine